Impact Of Giving Cucumber Juice Changes Blood Pressure In Elderly Hypertension Sufferers At Integrated Service Post For The Elderly “X” In Malang Regency - Sutiyarsih, Emy; Sulartri, Anastasia Sri; Ariesti, Ellia (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
Hypertension is known as a silent killer because many individuals are unaware that they have high blood pressure, which can lead to significant health complications and various diseases. Treatment modalities includes pharmacological intervention (medication) and non-pharmacological intervention (treatment without chemicals). Consuming fruits and vegetables rich in vitamins, water, and minerals such as cucumbers can be utilized as non-pharmacological treatments to manage blood pressure.  Cucumbers contain potassium, which helps to dilate blood vessels thereby reducing blood pressure. This study aims to determine the impact of administering cucumber juice to elderly individuals with hypertension. The research design employed quasi-experimental design, with the one group of pre-post-test method. The study included 30 respondents whose blood pressure was measured before and after consuming cucumber juice. The results were analyzed using Wilcoxon analysis test, with a p-value of 0.0001 0.05, indicating a significant impact of cucumber juice to elderly with hypertension. The Health Center is encouraged to implement and advocated for the use of cucumber juice as a non-pharmacological intervention for managing hypertension among the elderly.